Evaluation of clinical trials of ethnomedicine used for the treatment of diabetes: A systematic review - Elmi, Gul Rehman; Anum, Kamil; Saleem, Kalsoom; Fareed, Rameesha; Noreen, Sobia; Wei, Haiyan; Chen, Yongxing; Chakraborty, Avirup; Rehman, Masood Ur; Liyuan, Shi; Abbas, Muhammad; Duan, Yongtao (Frontiers in Pharmacology, 2023)
Diabetes mellitus (DM) is a widespread metabolic disorder with a yearly 6.7 million deaths worldwide. Several treatment options are available but with common side effects like weight gain, cardiovascular diseases, neurotoxicity, hepatotoxicity, and nephrotoxicity. Therefore, ethnomedicine is gaining the interest of researchers in the treatment of DM. Ethnomedicine works by preventing intestinal absorption and hepatic production of glucose as well as enhancing glucose uptake in muscles and fatty tissues and increasing insulin secretion. A variety of plants have entered clinical trials but very few have gained approval for use. This current study provides an evaluation of such clinical trials. For this purpose, an extensive literature review was performed from a database using keywords like “ethnomedicine diabetes clinical trial”, “clinical trials”, “clinical trial in diabetes”, “diabetes”, “natural products in diabetes”, “ethno-pharmacological relevance of natural products in diabetes”, etc. Clinical trials of 20 plants and natural products were evaluated based on eligibility criteria. Major limitations associated with these clinical trials were a lack of patient compliance, dose-response relationship, and an evaluation of biomarkers with a small sample size and treatment duration. Measures in terms of strict regulations can be considered to achieve quality clinical trials. A specific goal of this systematic review is to discuss DM treatment through ethnomedicine based on recent clinical trials of the past 7 years.